One-year follow-up of the nutritional status of patients undergoing liver transplantation - Maria Eugênia Deutrich Aydos (Nutrición Hospitalaria)
Background: Choosing the method of nutritional assessment is essential for proper follow-up of the nutritional status of patients undergoing liver transplantation. Objectives: Evaluate and compare the nutritional status of cirrhotic patients before and after liver transplantation over a year by different methods of nutritional assessment. Methods: Patients undergoing liver transplantation were assessed in five phases: pre-transplant, 1, 3, 6 and 12 months after transplantation at the hospital Santa Casa de Misericordia de Porto Alegre, RS, Brazil. The methods used for nutritional assessment were anthropometry, grip strength of the non-dominant hand (HGS) by dynamometry, thickness of the adductor pollicis muscle (APM) and phase angle (PA) by bioelectrical impedance analysis (BIA). In all evaluations, the same measurements were taken. Results: Evaluations were performed in 22 patients. Methods that showed a higher prevalence of malnourished patients before transplantation were PA by BIA (25%), arm muscle circumference (AMC) (21.9%) and arm circumference (AC) (18.8%). When comparing the nutritional status of patients during follow-up, there was a significant difference only in the evaluation methods AC, triceps skinfold thickness and PA by BIA. At the end, the methods of nutritional assessment were compared again. They showed a significant statistical difference, with HGS being the best method for detecting malnutrition. Conclusions: In conclusion, it is suggested that the method PA by BIA could be widely used with this population since the results are consistent with other findings in the literature and they are significant, reliable, and reproducible.